Online Driver Crisis In Dealing With Customers In Yogyakarta During Covid-19 Pandemic - Kristina Andryani (Universitas Ahmad Dahlan, 2021)
The pandemic situation in early 2020 was experienced by almost all regions in the world, including Indonesia. The pandemic has an extensive impact on the life of the country's economy, especially in terms of transportation or narrower transportation service for people, which is an online motorcycle application-based service with a smaller scope than other public transportation. The purpose of this paper is to see the crisis that occurs in drivers for services provided amid a pandemic situation like this with various binding rules related to the limitation of human movement from one place to another, which can even lead to crowds. The method used in searching for data was conducting in-depth interviews with several online motorcycle taxi drivers and group discussions to dig deeper into information, and the results obtained from this research were the best services that must be prioritized even though the rules and regulations during the PSBB period bind online motorcycle drivers. Several cases that went viral on social media related to orders that did not match could be addressed from the start by referring to the stages of crisis management, and by looking at the problems that occur, in the future, it is expected that the applicator can manage the problem into a well-patterned system.